DEVELOPING LEARNING MEDIA OF CROSSWORD PUZZLE TO IMPROVE STUDENTS’ VOCABULARY - Bastomi, Muhamamd Lutfi Rifki; Pratiwi, Wiwied; Zuniati, Mai; Irhamudin, Irhamudin (Institut Agama Islam Negeri (IAIN) Bone, 2024)
The objective of this study is 1) to develop learning media for crossword puzzles to improve vocabulary; 2) to determine the feasibility of learning media for crossword puzzles to improve vocabulary from material experts and media experts; and 3) to know the effectiveness of developing learning media for crossword puzzles to improve students’ vocabulary. The type of research used is research and development (R&D). The method used is the ADDIE development method. The research subjects involved are 8th grade students of Darul A’mal Metro MTs, for a total of 15 students. Based on the results of the research, it can be concluded that the learning medium of crossword puzzles to improve students’ vocabulary is effectively used in the teaching and learning process based on the N-Gain Score scores obtained with a score of 100% in the high category.